2019
DOI: 10.1109/tgrs.2018.2883495
|View full text |Cite
|
Sign up to set email alerts
|

Gaussian Process Regression for Forest Attribute Estimation From Airborne Laser Scanning Data

Abstract: While the analysis of airborne laser scanning (ALS) data often provides reliable estimates for certain forest stand attributes -such as total volume or basal area -there is still room for improvement, especially in estimating species-specific attributes. Moreover, while information on the estimate uncertainty would be useful in various economic and environmental analyses on forests, a computationally feasible framework for uncertainty quantifying in ALS is still missing. In this article, the species-specific s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…Thus, our findings suggested the use of BART rather than KNN for this specific application; this was in agreement with the study by Varvia et al [57], which reported that the Bayesian method exhibits better RMSE value than KNN in the total basal area and volume estimation. Hence, the BART algorithm seems to be a perfect option in forestry, where heterogeneity and spatial autocorrelation structures exist and might involve inconsistencies in the linearity, homogeneity, and independency of the variables [41].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, our findings suggested the use of BART rather than KNN for this specific application; this was in agreement with the study by Varvia et al [57], which reported that the Bayesian method exhibits better RMSE value than KNN in the total basal area and volume estimation. Hence, the BART algorithm seems to be a perfect option in forestry, where heterogeneity and spatial autocorrelation structures exist and might involve inconsistencies in the linearity, homogeneity, and independency of the variables [41].…”
Section: Discussionsupporting
confidence: 93%
“…Machine learning methods are regarded as popular and advanced models among the research communities. Their ability and flexibility of data modelling with a large set of variables together with their learning schemes and control over the non-linearity in the datasets have been tested and proved, especially in vegetation applications [38,57]. However, further investigations in terms of the various challenges and limitations of the ML algorithms is required.…”
Section: Machine Learning Methodsmentioning
confidence: 99%
“…We predicted the species-specific volumes using the multivariate Gaussian process (GP) regression [39]. The GP regression is a widely used machine learning method that is related to kriging and support vector machines.…”
Section: E Estimation Methodologymentioning
confidence: 99%
“…The predicted total volume was computed as a sum of the predicted species-specific volumes. The postprocessing of negative predictions was implemented, as presented in detail by Varvia et al [39].…”
Section: E Estimation Methodologymentioning
confidence: 99%
See 1 more Smart Citation